OXYGEN DELIVERY UNDER CONDITIONS OF ABDOMINAL SEPSIS IN THE PRESENCE OF A HIGH MORTALITY RISK - Kursov, S.V. (World of Medicine and Biology, 2012)
64 pre- and post operated patients with signs of abdominal sepsis, who had a high starting point of estimation of state severity acсording to the APACHE-II scale have been examined as to the oxygen delivery and consumption changes depending on the composition of infusion therapy. Advantage belonged to the derivatives of starch hydroxal, the introduction of which provided the largest amount of cases of reliable improvement of oxygen exchange indices.